Micelles modified with a chitosan-derived homing peptide for targeted intracellular delivery of ginsenoside compound K to liver cancer cells. (15th February 2020) - Zhang, Jianmei; Jiang, Yunyao; Li, Yeping; Li, Weibo; Zhou, Jing; Chen, Jianwen; Shang, Zhi; Gu, Qian; Wang, Wei; Shen, Ting; Hu, Weicheng
Graphical abstract: Highlights: APD-CK micelles were prepared as a delivery system for liver targeting using a self-assembly technique. APD-CK micelles displayed enhanced HepG2 and Huh-7 cellular accumulation in vitro . APD-CK micelles could enhance the cytotoxic and apoptotic potentials against two liver cancer cells. Abstract: Ginsenoside compound K (CK), a major metabolite of protopanaxadiol ginsenosides, exhibits significant anticancer activities against various cancer cells. However, CK has poor water solubility and low bioavailability, which have limited its application. In this study, A54 peptide was utilized to fabricate CK-loaded micelles (APD-CK) for liver targeting, using deoxycholic acid-O-carboxymethyl chitosan as the vehicle. The average particle size of APD-CK micelles was about 171.4 nm by dynamic light scattering in the hydrated state and their morphology were spherical with good dispersion. An in vitro release assay indicated pH-responsive and sustained release behavior through a mechanism of non-Fickian diffusion. Moreover, the in vitro cytotoxicity of the APD-CK micelles against HepG2 and Huh-7 cells was significantly stronger than that of CK up to 20 μg/mL. Enhanced cellular uptake of micelles in both cell types was established using confocal fluorescence scanning microscopy and flow cytometry. In addition, western blot analysis revealed that APD-CK micelles could promote the protein expression levels of caspase-3, caspase-9, and poly (ADP-ribose) polymerase. Therefore, APD-CK micelles are a potential vehicle for delivering hydrophobic drugs in liver cancer therapy, enhancing drug targeting and anticancer activity.